СУТНІСТЬ ПОНЯТТЯ “ЖИТТЄВИЙ ДОСВІД” ТА його ОСНОВНІ ХАРАКТЕРИСТИКИ (Педагогіка вищої та середньої школи, 2008)
The author in the article proves the necessity to harmonize knowledge and experience of preschool children as the conditions of child's individuality development. On the basis of scientific literature the essence of such phenomena as “experience”, “acquired experience”, “well-turned experience” and its main characteristics are revealed.